2021
DOI: 10.5539/ijef.v13n5p22
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Information & Communication Technology and Foreign Direct Investment Inflow to Africa

Abstract: This paper examined the relationship between the increasing Information & Communication Technology (ICT) infrastructure in Africa and foreign direct investment inflow to Africa using panel data sourced from ITU and WDI over 17 years (1998-2014). The paper applies both the fixed-effect and difference-in-differences models. The results indicate that there is a positive correlation between FDI inflow and ICT level in the host country.  The surge in ICT infrastructure in 2009 has substantially inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The rapid development of Information and Communication Technologies (ICT), represented by the Internet, has profoundly changed the way companies operate, their daily activities, and the way they do business. Research by scholars has found that ICT is an important influencing factor in the choice of FDI location [1][2][3][4][5] . Currently, there are more studies on the factors influencing the efficiency of OFDI in China, but little literature has focused on the impact of the level of ICT development in the host country on the efficiency of OFDI in China.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of Information and Communication Technologies (ICT), represented by the Internet, has profoundly changed the way companies operate, their daily activities, and the way they do business. Research by scholars has found that ICT is an important influencing factor in the choice of FDI location [1][2][3][4][5] . Currently, there are more studies on the factors influencing the efficiency of OFDI in China, but little literature has focused on the impact of the level of ICT development in the host country on the efficiency of OFDI in China.…”
Section: Introductionmentioning
confidence: 99%